Spirituality and Contemporary Higher Education. Issue 3 (2nd July 2016) - Waggoner, Michael D.
Abstract: Though religion played a central role in the founding of U.S. higher education, over the centuries, its influence was diluted by competing secular emphases. In recent decades, religion has seen a resurgence in academic and co-curricular attention on campuses. In addition, a spirituality not based on religion has gained increasing attention. The aim of this article is to provide an overview of the phenomenon of spirituality in contemporary higher education. The author discusses the recent appearance of spiritualty on campus, relates what research says about the potential benefits of and challenges in addressing spirituality in higher education, and examines some of the ways in which it is being addressed on U.S. college campuses.